WEB-BASED INVENTORY SYSTEM DEVELOPMENT WITH AGILE AT CV DAZRY HARAPAN - Saputra, Muhammad Hadi; Dristyan, Febri; Handoko, Dedi (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: Dazry Harapan Household Industry (IRT) is an SME in Jambi City specializing in the production of laundry perfume and previously relied on manual record-keeping using notebooks. This conventional method created several issues, including frequent stock recording errors, difficulties in preparing financial reports, delays in identifying minimum stock levels, and the absence of structured historical data. This study aims to develop a web-based digital recording system to improve efficiency, accuracy, and transparency in inventory management. The system was developed using the Agile (Scrum) methodology through three sprints covering the creation of login modules, stock and transaction recording, reporting, minimum-stock notifications, and interface refinement. System design was formulated using use case diagrams, flowcharts, database modeling, and interface prototypes based on the Laravel framework. User Acceptance Testing (UAT) demonstrated high user satisfaction, with 90% of respondents stating that the system is easy to use, 85% reporting faster administrative processes, and 95% acknowledging improved reporting accuracy. The system also increased recording efficiency by 66%—from 3 minutes to 1 minute per transaction—and reduced stock recording errors from 15% to 2% per month. The results indicate that implementing a web-based digital recording system significantly enhances the operational performance of SMEs. Keywords: SMEs, digital recording system, Agile, inventory management, Laravel. Abstrak: Industri Rumah Tangga (IRT) Dazry Harapan merupakan UMKM di Kota Jambi yang bergerak pada produksi parfum laundry dan masih menggunakan sistem pencatatan manual berbasis buku tulis. Metode konvensional tersebut menimbulkan berbagai permasalahan, seperti tingginya kesalahan pencatatan stok, hambatan dalam penyusunan laporan keuangan, keterlambatan identifikasi stok minimum, serta ketiadaan rekap data historis yang terstruktur. Penelitian ini bertujuan mengembangkan sistem pencatatan digital berbasis web untuk meningkatkan efisiensi, akurasi, dan transparansi manajemen persediaan. Pengembangan dilakukan menggunakan metode Agile (Scrum) melalui tiga sprint yang mencakup pembangunan modul login, pencatatan stok, transaksi, laporan, notifikasi stok minimum, serta penyempurnaan antarmuka. Desain sistem dirumuskan menggunakan use case diagram, flowchart, perancangan database, dan prototipe antarmuka berbasis Laravel. Hasil pengujian melalui User Acceptance Test (UAT) menunjukkan tingkat penerimaan pengguna yang tinggi, yaitu 90% menilai sistem mudah digunakan, 85% merasakan percepatan proses pencatatan, dan 95% menilai laporan yang dihasilkan lebih akurat. Efisiensi waktu pencatatan meningkat sebesar 66%, dari 3 menit menjadi 1 menit per transaksi, sedangkan tingkat kesalahan pencatatan menurun dari 15% menjadi 2% per bulan. Penelitian ini membuktikan bahwa implementasi sistem pencatatan digital berbasis web mampu meningkatkan kualitas operasional UMKM secara signifikan. Kata kunci: UMKM; sistem pencatatan digital; Agile; manajemen stok; Laravel;